2020
DOI: 10.1177/1077801219893475
|View full text |Cite
|
Sign up to set email alerts
|

Military Cohorts, Substance Use, and Male-Perpetrated Intimate Partner Violence

Abstract: This study considers variations of intimate partner violence (IPV) from the point of the perpetrator to test the impact of demographic factors on the type of IPV most prevalent among pre-9/11 and post-9/11 military families from the National Longitudinal Study of Adolescent to Adult Health (1994–2008): Waves I and IV in-home interviews ( N = 499). Study findings indicate that the perpetration of physical and sexual IPV depends on the context of veteran cohort and race/ethnicity. Models for substance use and IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…When conflict arises within their relationships, veterans or service members may respond violently, reflecting military conditioning. In the end, IPV perpetrators may have feelings of guilt or disconnection that potentially contribute to poorer mental health status, and subsequently higher AOD use/ misuse (Cancio, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When conflict arises within their relationships, veterans or service members may respond violently, reflecting military conditioning. In the end, IPV perpetrators may have feelings of guilt or disconnection that potentially contribute to poorer mental health status, and subsequently higher AOD use/ misuse (Cancio, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is no overarching theory that explains why interracial relationships face an elevated risk of violence (Cancio, 2021); in this study, we have created validated a priori measures of relevant concepts and constructs. We found that (a) White and Black veterans are more violent in monoracial relationships, meanwhile, Latino veterans have a higher IPV prevalence in interracial relationships; (b) Black and White veterans were more likely to use AOD after IPV perpetration in interracial relationships, in contrast, Latino veterans use AOD in monoracial relationships; (c) veteran mental health status was affected after perpetration of IPV, similar to the effects experienced after combat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This social and psychological conditioning into military life includes hyperactive vigilance to perceived threats and emotional distancing from others (Cancio, 2015). The desensitization of service members may influence MSV behaviors (Cancio, 2020).…”
Section: Literaturementioning
confidence: 99%
“…Other military-related factors (e.g., exposure to combat, the number of deployments, traumatic brain injury) may also influence MSV behaviors (Cancio, 2020). Military contexts (e.g., military jobs) and stressors (e.g., fear of death or harm) may make service members particularly vulnerable to MSV-related risky behaviors (Cancio, 2017).…”
Section: Literaturementioning
confidence: 99%